Florida's Large Carnivores - Martin B. Main; Ginger Allen; Melvin E. Sunquist (EDIS)
This document provides an overview of Floridas four largest carnivores: the Florida panther, black bear, bobcat, and the coyote. This document is Fact Sheet WEC 183, one of a series of the Department of Wildlife Ecology & Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: June 2004.